First record of Permo-Triassic palynomorphs of the N'Condedzi sub-basin, Moatize-Minjova Coal Basin, Karoo Supergroup, Mozambique - Galasso, Francesca (2019)
Permian-Triassic ages have been identified for the first time in the Karoo Supergroup of the N'Condedzi sub-basin, Moatize-Minjova Coal Basin, Mozambique. This transition was identified in a coal exploration borehole that penetrated the Matinde and Cadzi formations. The top of the Matinde Formation is dated latest Permian (Lopingian), and the Cadzi Formation is attributed to Triassic based on palynostratigraphy. The Lopingian age is established by the identification of three palyno-assemblages: Assemblage L1 based on the first occurrence (FO) of Guttulapollenites pollen, Assemblage L2 is marked by the FO of Thymospora pseudothiessenii, and Assemblage L3 is defined by the FO of Osmundacidites senectus. Triassic palynomorphs were identified for the first time in Mozambique (Karoo basins). The data allowed the identification of three assemblages: Assemblage T1 defined by the FO of Densoisporites nejburgii of Induan age, Assemblage T2 is marked by the FO of Platysaccus queenslandi and assigned to the Olenekian age, and Assemblage T3 is defined by the FO of Samaropollenites speciosus and Enzonalasporites vigens, indicating a Carnian age. No Middle Triassic rocks were identified, and the early Triassic sediments are overlain by sedimentary rocks of Carnian age, a hiatus that may correspond to an important tectonic event with uplift and erosion. This tectonic event is also suggested by the occurrence of common reworked Permian palynomorphs in the Carnian sedimentary rocks. These new data constrain the age of the Karoo Supergroup formations of Mozambique and contribute to improve the palaeoecological, palaeoclimatic evolution, and the palaeogeographic position of the Karoo Mozambique basins within the Gondwana supercontinent. (C) 2019 Elsevier Masson SAS. All rights reserved.